Impression management of buzzer in social media twitter - Suryandari, Nikmah; Lutviana, Vivi (Jurnal Studi Komunikasi, 2020)
This study aimed to find out the Impression Management of buzzers on Twitter social media. The methodology in this research was qualitative net-nography in which data were collected through online observation and interviews as well as literature studies. The subject of the research was the buzzers, and the object was the buzzer impression management, while the location of the research was on Twitter social media. The results of this study provided an overview of how buzzers did impression management on social media twitter. We found that the buzzers did impression management through message content, using other terms replace ‘buzzer’, emphasising the truth of message content, using social media accounts as self-identity, and reviewing products and events as a form of impression management.